Heavy metals contamination in sediments of Bharalu river, Guwahati, Assam, India: A tributary of river Brahmaputra. - Rajashree Bhuyan; Pinki Brahma; Mayuri Chabukdhara; Neha Tyagi; Sanjay Kumar Gupta; Tabarak Malik (PLoS ONE, 2023)
This study aimed to assess heavy metals in the surface sediments of the Bharalu river, India. Metal concentrations ranged from 6.65-54.6 mg/kg for Ni, 25.2-250.0 mg/kg for Zn, 83.3-139.1 mg/kg for Pb, and 11940.0-31250.0 mg/kg for Fe. The level of metal contamination was assessed using sediment quality guidelines, geo-accumulation index (Igeo), enrichment factor (EF), pollution Load Index (PLI),Nemerow's pollution index (PIN), and potential ecological risk index. Pb exceeded the sediment quality guidelines at all sites indicating a potential threat to the river ecosystem. (Igeo) and EF also showed moderate to severe enrichment for Pb. Potential ecological risk (RI) showed low risk in the sediments, and Pb is the major contributor to ecological risk. Overall, pollution indices revealed comparably higher contamination of the sediments in the downstream sites than in the upstream site. PCA and correlation matrix analysis indicated both anthropogenic and natural origins for metals. Among anthropogenic sources, urban discharges and waste dumping could be mainly attributed to metal contamination in the river sediments. These findings may aid in developing future river management methods explicitly aimed at tackling heavy metal pollution to prevent further damage to the river ecosystem.